Editorial: Bringing light into deep-sea biodiversity - Arbizu, Pedro Martínez; Brix, Saskia (Zootaxa, 2008)
Despite the fact that oceans cover over 70% of the earth’s surface, only about one third of all currently known species have been described from marine ecosystems (Reaka-Kudla 1997, Groombridge & Jenkins 2000, Grassle 2001, Boltovskoy et al. 2005). We believe that this represents an underestimation of the real biodiversity in the oceans (Bouchet 2006). Since the year 2000, the “Census of Marine Life” (CoML, www.coml.org), an international initiative involving more than 2000 researchers from 80 nations, is putting a huge effort into describing and understanding patterns of species richness and distribution in all ocean realms. The deep sea is one of the largest ecosystems on earth and probably harbours a substantial amount of biodiversity. The fraction of new species to be found in deep-sea areas visited for the first time ranges from 50 to 100 % (Wilson 1980, Poore et al. 1994, Park 2000, Brandt et al. 2004, Brandt et al. 2007a,b), with most of them only being represented by single individuals in the samples (Rose et al. 2005, Brandt et al 2007a,b,). This fact, together with the logistic impediments of sampling in abyssal plains, constrains our knowledge of the life in the hidden depths of the ocean.